Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Sebagai Variabel Intervening Pada BSI Kcp Nagan Raya 2 - Hajar, Siti; Badawi, Khalil (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to use a quantitative approach to the phenomena that occur at Bank Syariah Indonesia Kcp Nagan Raya 2. The data method used in this study is the Total Sampling technique with a sample of 66 customers at BSI Kcp Nagan Raya 2. The data used are Primary data and Secondary data. The data analysis techniques that will be used are Validity Test, Reliability Test, Classical Assumption Test, Simple Regression Analysis Test, Hypothesis Testing using SPSS22 Software and Determination Coefficient. From the results of the Customer Satisfaction Path Analysis Test, it is able to mediate the relationship between Service Quality and Customer Loyalty with a direct influence value of 0.023 and an indirect influence of 0.1406, which means that the indirect influence value is greater than the direct influence value. These results indicate that indirectly X through Y has a significant influence on Z.